2008
DOI: 10.1111/j.1600-6143.2008.02321.x
|View full text |Cite
|
Sign up to set email alerts
|

The Role of the IL23/IL17 Axis in Bronchiolitis Obliterans Syndrome After Lung Transplantation

Abstract: Bronchiolitis obliterans syndrome (BOS) is the leading cause of death after lung transplantation. Treatment is challenging, as the precise pathophysiology remains unclear.We hypothesize that T H 17 lineage plays a key role in the pathophysiology of BOS by linking T-cell activation to neutrophil influx and chronic inflammation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
155
0
1

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 156 publications
(161 citation statements)
references
References 49 publications
(66 reference statements)
5
155
0
1
Order By: Relevance
“…CD4þ Th17 cells can promote acute allograft rejection and vasculopathy in animals models (12). In lung transplant recipients, studies have shown that the IL23/IL17 axis is involved in patients with bronchiolitis obliterans syndrome (BOS) (13,14). In kidney transplantation, IL-17 transcripts are observed in kidney transplant biopsy specimens presented with rejection (15).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…CD4þ Th17 cells can promote acute allograft rejection and vasculopathy in animals models (12). In lung transplant recipients, studies have shown that the IL23/IL17 axis is involved in patients with bronchiolitis obliterans syndrome (BOS) (13,14). In kidney transplantation, IL-17 transcripts are observed in kidney transplant biopsy specimens presented with rejection (15).…”
Section: Discussionmentioning
confidence: 99%
“…Calcineurin inhibitors, steroids, and other commonly used immunosuppressive drugs have little or no effect on the IL-17 signaling pathway. Surprisingly, studies of lung transplantation have shown that macrolide antibiotics (azithromycin and erythromycin) inhibit the progression of Th17-mediated BOS (13,29). However, it is still not clear whether such a strategy could be a useful additional therapy for TCMR in the recipients of kidneys from elderly donors.…”
Section: Discussionmentioning
confidence: 99%
“…For BAL, two aliquots of sterile 50 mL saline were instilled in the right middle lobe or lingula. The returned fractions were pooled and processed as previously described (13). Total and differential cell counts are routinely performed in the lab as previously reported (13).…”
Section: Lung Function Bal and Bronchoscopymentioning
confidence: 99%
“…The returned fractions were pooled and processed as previously described (13). Total and differential cell counts are routinely performed in the lab as previously reported (13). Another fraction was immediately centrifuged at 500g for 10 min at 4° and then stored at -80°C.…”
Section: Lung Function Bal and Bronchoscopymentioning
confidence: 99%
“…Следует развивать современные знания о влия нии клеточного старения трансплантата (ускоренно го старения) на его функцию и риск развития СОБ, а также о роли интерлейкина 17 [150][151][152][153][154][155][156], аутоим мунных механизмов, популяций регуляторных лим фоцитов [157][158][159][160][161][162][163], нейтрофильного ответа и меха низмов, приводящих к фиброзу дыхательных путей при гипотетическом феномене эпителиально мезен химальной трансформации (который пока остается гипотетическим и недостаточно хорошо доказан на моделях животных) [164][165][166][167]. При помощи этой информации возможно разработать новые методы терапии, направленные на предотвращение и лече ние СОБ.…”
Section: ключевые нерешенные вопросы и направления дальнейших исследоunclassified